APOE ε4 carrier status moderates the effect of lifestyle factors on cognitive reserve - O'Shea, Deirdre M.; Zhang, Andrea S.; Rader, Katana; Shakour, Rebecca L.; Besser, Lilah; Galvin, James E. (Alzheimer's & dementia, 2024)
INTRODUCTION This study examines the role of lifestyle factors in cognitive reserve among older adults, focusing on the moderating effect of apolipoprotein E (APOE) ε4 status. METHODS Data from 157 participants aged 45 and older from the Healthy Brain Initiative (HBI) were analyzed. Cognitive reserve was estimated using residual scores from Cognivue Clarity tests after accounting for brain atrophy and white matter hyperintensities (WMHs). Lifestyle factors included education, occupational attainment, physical activity, social engagement, diet, and mindfulness. Structural equation models were conducted to assess interactions. RESULTS Significant interactions were found between APOE ε4 status and mindfulness and social engagement on cognitive reserve, indicating stronger associations for APOE ε4 carriers. DISCUSSION APOE ε4 carriers may benefit more from certain lifestyle factors, potentially through stress reduction and anti‐inflammatory pathways. These findings support integrating APOE ε4 genetic screening into personalized prevention strategies to enhance interventions aimed at preserving cognitive function and delaying dementia onset in at‐risk populations. Highlights Mindfulness and social engagement have increased cognitive reserve in APOE ε4 carriers. Study uses residual scores from Cognivue Clarity tests to estimate cognitive reserve. APOE ε4 carriers show stronger associations with certain lifestyle factors on cognitive reserve. Personalized interventions could enhance cognitive resilience in genetically at‐risk populations. Comprehensive assessment of multiple lifestyle factors highlights targeted intervention benefits.